Hydrophobicity of graphene as a driving force for inhibiting biofilm formation of pathogenic bacteria and fungi. Issue 3 (March 2019) - Agarwalla, Shruti Vidhawan; Ellepola, Kassapa; Costa, Mariana Caldeira Ferraz da; Fechine, Guilhermino José Macêdo; Morin, Julien Luc Paul; Castro Neto, A.H.; Seneviratne, Chaminda Jayampath; Rosa, Vinicius
Abstract: Objective: To evaluate the surface and wettability characteristics and the microbial biofilm interaction of graphene coating on titanium. Methods: Graphene was deposited on titanium (Control) via a liquid-free technique. The transfer was performed once (TiGS), repeated two (TiGD) and five times (TiGV) and characterized by AFM (n = 10), Raman spectroscopy (n = 10), contact angle and SFE (n = 5). Biofilm formation (n = 3) to Streptococcus mutans, Enterococcus faecalis, Pseudomonas aeruginosa and Candida albicans was evaluated after 24 h by CV assay, CFU, XTT and confocal microscopy. Statistics were performed by one-way Anova, Tukey's tests and Pearson's correlation analysis at a pre-set significance level of 5 %. Results: Raman mappings revealed coverage yield of 82 % for TiGS and ≥99 % for TiGD and TiGV. Both TiGD and TiGV presented FWHM > 44 cm −1 and ID /IG ratio < 0.12, indicating multiple graphene layers and occlusion of defects. The contact angle was significantly higher for TiGD and TiGV (110° and 117°) comparing to the Control (70°). The SFE was lower for TiGD (13.8 mN/m) and TiGV (12.1 mN/m) comparing to Control (38.3 mN/m). TiGD was selected for biofilm assays and exhibited significant reduction in biofilm formation for all microorganisms compared to Control. There were statistical correlations between the high contact angle and low SFE of TiGD and decreased biofilm formation. Significance: TiGD presented high quality and coverage and decreased biofilm formation for all species. The increased hydrophobicity of graphene films was correlated with the decreased biofilm formation for various species.